Space explorers - Moore, Eva.; Enik, Ted; Cole, Joanna (New York : Scholastic, 2000)
Carlos and his classmates join Ms. Frizzle on an expedition to outer space where they learn about the solar system.
560
Keywords: Outer space -- Fiction; Field trips -- Fiction; Adventure fiction